Acute sacral nerve stimulation reduces visceral mechanosensitivity in a cross‐organ sensitization model. Issue 4 (7th November 2016) - Langlois, L. D.; Le Long, E.; Meleine, M.; Antor, M.; Atmani, K.; Dechelotte, P.; Leroi, A. M.; Gourcerol, G.
Abstract: Background: Sacral nerve stimulation (SNS) is a surgical treatment of fecal and urinary incontinence that consists of inserting a stimulating electrode into one of the s3 or s4 sacral holes. In addition to the benefit of SNS in the treatment of incontinence, recent studies showed that SNS is effective in the treatment of irritable bowel syndrome as well as bladder pain syndrome. The aim of this study was to evaluate the effect of SNS on visceral mechanosensitivity in a cross‐organ sensitization rat model. Methods: Hypersensitive model was obtained by instillation of acetic acid into the bladder of rats during 5 minutes, 30 minutes before the start of the experiments. Visceral sensitivity was assessed by monitoring the change in mean arterial pressure in response to graded isobaric colorectal distension series. To decipher the mechanisms underlying SNS effect, rats were administered intravenously either a nonselective opioid receptor antagonist (naloxone) or a nitric oxide synthesis antagonist (L‐NAME). Neuronal activation in the dorsal horn of the sacral spinal cord was measured by counting c‐fos immunoreactive cells in response to colorectal distension and NMS. Key Results: Intravesical acetic acid instillation increased mean arterial pressure variation in response to colorectal distension when compared to saline group. SNS reduced the variation in arterial pressure. Colorectal distension induced a rise in c‐fos immunoreactive cells in the dorsal horn of the spinal cord. This effect was reduced by SNS. Conclusions & Inferences: SNS reduces visceral mechanosensitivity in a cross‐organ sensitization model. Abstract : Sacral nerve stimulation reduced colonic nociception in a rat model of cross‐organ sensitization. This effect involved an endogenous opioid pathway.